Artificial Reactor with Alterable Tandem Channeling for the Formation of Self‐Screened Catalytic Ability. Issue 2 (17th December 2019) - Pu, Lei; Wei, Wenjing; Zhu, Maiyong; Wu, Shuping; Shen, Xiaojuan; Li, Songjun
Abstract: Inspired by the polymeric "soft" properties and divisional isolation of tandem processes in natural systems, an artificial reactor with self‐screened catalytic ability was fabricated with a polymeric tri‐layer architecture. The non‐responsive middle layer encapsulated catalytic metal nanoparticles, while the two outer layers consisted of a negatively and a positively thermosensitive imprinted polymer. The inverse responsiveness of the outer layers induced switchable shapes, which led to alterable tandem channeling to the reactive middle layer and, as a result, the divisional admission of different substrates. This way, the reactor led to the formation of self‐screened catalytic ability. The design for this artificial reactor offers promising prospects for struggling tandem catalysts, suggesting opportunities to develop schedulable tandem processes. Abstract : Inspired by nature, an artificial reactor was fabricated with a polymeric tri‐layer architecture. The inverse responsiveness of the two imprinted outer layers induced switchable shapes in this artificial reactor. As a result, alterable tandem channeling to the reactive middle layer allowed divisional admission of different substrates, leading to self‐screened catalytic ability. The strategy of developing artificial reactors may be employed to formulate schedulable tandem catalytic processes.